2010
DOI: 10.1007/s00535-010-0241-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease in children: current trends

Abstract: Once considered rare in the East, inflammatory bowel disease (IBD) is now recognized to be an emerging entity in that region. East or West, the clinical features of and treatment options for IBD are the same, but it is possible that the exact pathogeneses or the initiating events differ. In this review, existing knowledge of IBD and new discoveries in the epidemiology, genetics and treatment of IBD are discussed in detail. The diagnosis and management of IBD in children has changed dramatically over the last d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 76 publications
1
18
0
10
Order By: Relevance
“…States (1)(2)(3). In 2008, the direct costs associated with the disease exceeded 6.8 billion dollars (4), and furthermore, the worldwide prevalence of IBD appears to be increasing (5).…”
Section: In the Unitedmentioning
confidence: 99%
“…States (1)(2)(3). In 2008, the direct costs associated with the disease exceeded 6.8 billion dollars (4), and furthermore, the worldwide prevalence of IBD appears to be increasing (5).…”
Section: In the Unitedmentioning
confidence: 99%
“…More recent basic and clinical research indicates that the chronic inflammatory reaction of the intestinal mucosa is directed against the gut microbiota in individuals with genetic and/or environmental susceptibilities. Disease onset occurs typically during young adulthood (25-35 yr), although ϳ20 -25% of cases are diagnosed during childhood (93). On a clinical basis, two major subtypes of IBD are defined as Crohn's disease (CD), which potentially affects any part of the gastrointestinal tract from the mouth to the anus, and ulcerative colitis (UC), an inflammatory condition limited to the colonic mucosa.…”
mentioning
confidence: 99%
“…Pediatric IBD patients form a separate group not only because of distinct disease characteristics and perhaps distinct genetic predispositions (93), but also because of differences in their bone metabolism. During the prepubescent and early pubescent period, bone modeling is the predominant form of skeletal growth, and the activities of osteoblasts and osteoclasts are not coupled.…”
mentioning
confidence: 99%
“…Although the exact frequency of the small bowel (SB) CD is unknown, most gastroenterologists believe that its prevalence has been underestimated and that it may have an increased incidence among children and young adolescents [2] . A recent study performed in pediatric patients with magnetic resonance (MR) enterography [3] , according to previous studies [4] , confirmed that the involvement of the terminal ileum is common to more than three times compared to that of the jejunum and the rest of the ileum. Moreover, the involvement of the jejunum alone is uncommon and it is more difficult to investigate because of its tendency to stay non distended [3] .…”
Section: Introductionmentioning
confidence: 96%
“…The clinical importance of the SB CD phenotype is the impact that a diffuse SB disease is expected to have on a child's growth and development. Moreover, patients with SB CD are more likely to experience complications, including intestinal obstruction and less commonly fistulization [4,5] . Thus, objective evaluation of the SB is essential in differentiating CD from other enteropathies and in directing the management of the patients with inflammatory bowel disease (IBD) [6,7] .…”
Section: Introductionmentioning
confidence: 99%